2012
DOI: 10.1080/00207233.2012.732751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cement factory operations on air quality and human health in Ewekoro Local Government Area, South-Western Nigeria

Abstract: The concentrations of pollutants associated with cement production and the effects on ambient air and community health were assessed in this study. Suspended particulates were monitored using a Negretti 1000 TM air sampler. Additionally, an Ogawa TM sampler was employed to assess levels of selected gaseous pollutants at selected sites. To collect data on health status, a questionnaire survey was used for selected neighbouring communities and clinic records for industry workers. The data were analysed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 14 publications
2
21
1
1
Order By: Relevance
“…Oguntoke et al 17 in their study on Impact of cement factory operations on air quality and human health in Ewekoro Local Government Area, South-Western Nigeria, found that the health profile of the factory workers and some residents of neighbouring communities showed high levels of respiratory and skin infections. Earlier studies 11,13,15,18 focused on cement factory workers or measured respirable dust concentration to which the workers were exposed to within the factory 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oguntoke et al 17 in their study on Impact of cement factory operations on air quality and human health in Ewekoro Local Government Area, South-Western Nigeria, found that the health profile of the factory workers and some residents of neighbouring communities showed high levels of respiratory and skin infections. Earlier studies 11,13,15,18 focused on cement factory workers or measured respirable dust concentration to which the workers were exposed to within the factory 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the non-exposed community (as well as the exposed) is located in the northern fringes of the Nigeria close to the Sahara desert. Earlier studies have shown that cement dust exposure in the factory 11,17 or in the community 17 led to higher prevalence of illnesses such as cough, phlegm, breathlessness, wheeze, shortness of breath with wheeze, chest pain, skin lesions and conjunctivitis. This high prevalence of illnesses as a result of chronic cement dust exposure could be as a result of the nature of cement which is highly alkaline; (P H 12-13) 7 its setting process is exothermic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] Oguntoke and his colleagues in their study in Ewekoro Local Government Area, South-Western Nigeria on both cement factory workers and residents of Ewekoro found that the health profile of the factory workers and some residents of neighbouring communities showed high levels of respiratory and skin infections. 12 A study carried out on the workers of this cement factory in Kalambaina found that cement dust was deleterious to health of the workers. 6,7 The study found the vital capacity and forced expiratory volume for one second percent [FEV 1 %] were found to be significantly lower in the cement factory workers than in the control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Some workers have postulated that cement dust is inert and harmless to humans and animals. In a 1987 review of literature, Holt 12 reported that Portland cement has no adverse effect on health of cement workers in England. Some reports support this view.…”
Section: Introductionmentioning
confidence: 99%